Probabilistic 2D Point Interpolation and Extrapolation via Data Modeling (Informatica, 2015)
Mathematics and computer science are interested in methods of 2D curve interpolation andextrapolation using the set of key points (knots). A proposed method of Hurwitz- Radon Matrices (MHR)is such a method. This novel method is based on the family of Hurwitz-Radon (HR) matrices whichpossess columns composed of orthogonal vectors. Two-dimensional curve is interpolated via differentfunctions as probability distribution functions: polynomial, sinus, cosine, tangent, cotangent, logarithm,exponent, arcsin, arccos, arctan, arcctg or power function, also inverse functions. It is shown how tobuild the orthogonal matrix operator and how to use it in a process of curve reconstruction.